Role of the pulsed dye laser in the management of ulcerated capillary haemangiomas. Issue 2 (February 1996) - Lacour, M; Syed, S; Linward, J; Harper, J I
Abstract : A complication of capillary haemangiomas is ulceration, which may arise after trauma and/or infection. Until recently, conservative management was the rule. However, the recent advent of the pulsed dye laser has revolutionised the treatment of vascular birthmarks and provided a new tool for the management of capillary haemangiomas. Thirteen cases of ulcerated capillary haemangiomas referred to our department were reviewed; five were treated conservatively and eight were treated with the laser. Those treated with the laser had all failed conservative management and healed completely within one to four weeks. Remarkably rapid alleviation of pain was achieved. For those haemangiomas around the mouth and perineum, laser treatment enabled early restoration of normal feeding, micturition, and defaecation. It is therefore recommended that if ulcerated capillary haemangiomas do not improve after a short period of optimal conservative treatment, laser treatment should be considered.